PERFORMANCE ANALYSIS OF COMPOUND PARABOLIC CONCENTRATOR INTEGRATED WITH EVACUATED TUBE RECEIVER USING HYBRID NANOFLUIDS - NASEER, HARIS (2021)
Water, glycols, and thermal oils are employed as heat transfer fluids in solar thermal collectors.